1999
DOI: 10.1002/(sici)1097-4679(199905)55:5<539::aid-jclp2>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

The hope construct, will, and ways: Their relations with self-efficacy, optimism, and general well-being

Abstract: This investigation (N = 204) examined (a) the relations between the hope construct (Snyder, Harris et al., 1991; Snyder, Irving, & Anderson, 1991) and its two essential components, "will" and "ways," and the related constructs of self-efficacy and optimism; and (b) the ability of hope, self-efficacy, and optimism to predict general well-being. Maximum-likelihood factor analysis recovered will, ways, self-efficacy, and optimism as generally distinct and independent entities. Results of multiple regression analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
118
1
5

Year Published

2002
2002
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 503 publications
(136 citation statements)
references
References 26 publications
5
118
1
5
Order By: Relevance
“…Both hope-self and hope-other are positively correlated with self-esteem and optimism, which is good evidence of convergent validity of this instrument and corroborates findings reported by several authors that reported similar results (Carver & Scheier, 2002;Magaletta & Oliver, 1999;Stajkovic, 2006). However, hope-self was more closely associated with the other constructs than hope-other.…”
Section: Discussionsupporting
confidence: 90%
“…Both hope-self and hope-other are positively correlated with self-esteem and optimism, which is good evidence of convergent validity of this instrument and corroborates findings reported by several authors that reported similar results (Carver & Scheier, 2002;Magaletta & Oliver, 1999;Stajkovic, 2006). However, hope-self was more closely associated with the other constructs than hope-other.…”
Section: Discussionsupporting
confidence: 90%
“…is the role assumed for perceptions of personal agency" (p. 288). Yet, Magaletta and Oliver (1999) found that the agency part of hope (as noted in the preceding quote) was empirically indistinguishable from optimism. Magaletta and Rocco (1997) also could not empirically differentiate the pathways part of hope from optimism.…”
Section: The Similarities Among the Manifestations Of Core Confidencementioning
confidence: 93%
“…These and others either emphasize the agency or the pathways, but not both equally as does hope. Studies have clearly shown that hope has discriminant validity among positive psychological constructs (Magaletta & Oliver, 1999;Scioli et al, 1997).…”
Section: Hope As the Most Unique Pob Capacitymentioning
confidence: 99%